Aristotelian truth in administrative procedure and administrative court proceedings - Gontarski, Waldemar (Acta Universitatis Lodziensis. Folia Iuridica, 2014)
The contemporary truth reconstructed in a trial reflects differences between the Aristotelian truth in terms of its essence and criterion (material truth – veritas est adaequatio rei et intellectus – ad Aristotle, The Metaphysics IV.7.[1011b 26-27])- and its practical realisation (objective truth – in medio stat veritas – ad Aristotle, Nicomachean Ethics II.7.[1108a 19–20]). In a non-adversarial processes – such as the Polish criminal trial - as opposed to the Anglo-Saxon one - the Polish administrative procedure (an administrative court has only a controlling function, not a reformative one and does not ascertain facts on its own) or separate proceedings in the Polish civil procedure – the court is expressis verbis obliged to reconstruct the objective truth (i.e. the truth which can be ascertained by a man meeting the diligentia boni patris familias standard) and not the material truth. Nonetheless, if the judicial truth understood in this way (the truth ascertained by the court; if the court does not demonstrate an evidential initiative, then it will not ascertain the truth, but it will merely assess the reliability of the evidence submitted as in the Anglo-American criminal trial) will differ from the material truth, it can act as a statutory premise to resume the proceedings. That is, generally speaking, the main difference between the inquisitorial and the adversarial models.